The Task, and Other Poems - Cowper, William, 1731-1800 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Task, and Other Poems" by William Cowper is a collection published in 1785, featuring his masterwork "The Task: A Poem, in Six Books." Beginning playfully with the sofa's origins, this blank verse meditation explores nature's blessings, retired life, and religious faith while attacking slavery, blood sports, and social frivolity. Written in unusually conversational language for its era, the poem deeply influenced writers from Robert Burns to Jane Austen and the Lake Poets, capturing the Evangelical spirit of its age. (This is an automatically generated summary.)
The Task -- The Diverting History of John Gilpin -- An Epistle to Joseph Hill, Esq. -- To Mary.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Task_(poem)
Release date is 2003-01-01
This eBook was produced by Les Bowler, St. Ives, Dorset
Keywords: English poetry -- 18th century